Gender Difference is Associated with Short-Term Outcomes in Non-Surgically Managed Acute Aortic Dissection Patients with Hypertension: A Retrospective Cohort Study - Zhou Y; Peng W; Yang G; Pan X; Ding N; Zhang H; Peng Z; Zhang D; Wu S; Chai X (Dove Medical Press, 2021)
Yang Zhou,1,2,* Wen Peng,1,2,* Guifang Yang,1,2 Xiaogao Pan,1,2 Ning Ding,1,2 Hongliang Zhang,1,2 Zhenyu Peng,1,2 Dongshan Zhang,1,2 Sijie Wu,3 Xiangping Chai1,2 1Department of Emergency Medicine, The Second Xiangya Hospital, Central South University, Changsha, People’s Republic of China; 2Emergency Medicine and Difficult Diseases Institute, Central South University, Changsha, People’s Republic of China; 3Department of Cardiovascular Surgery, The Second Xiangya Hospital, Central South University, Changsha, People’s Republic of China*These authors contributed equally to this workCorrespondence: Sijie Wu; Xiangping ChaiThe Second Xiangya Hospital of Central South University, 139 Renmin Road, Changsha, Hunan Province 410011, People’s Republic of ChinaEmail wusijie0605@sina.com; chaixiangping@csu.edu.cnBackground: The management of acute aortic dissection (AAD) has improved; however, the outcomes related to different gender with short-term outcomes in non-surgically managed AAD with hypertension are still limited. Our objective was to explore gender-differences in association with short-term outcomes of patients comorbid with hypertension in non-surgically managed AAD.Methods: This is an observational retrospective single-center cohort. We analyzed the data from the Second Xiangya Hospital of Central South University (2014– 2018). The data on demographics, clinical presentation, chronic comorbidities, laboratory testing, imaging studies, and treatment were analyzed for all patients. Univariate and multiple analyses were used to test gender-difference associated with short-term outcomes of patients with hypertension in non-surgically managed AAD.Results: In total, 288 patients were enrolled in this study, of whom 238 (82.63%) were male and 50 (17.37%) were females. About 74% of female patients were dead in-hospital, which was more than male patients (56.3%). Female patients with diabetes mellitus were more than male patients (14% vs 2.94%), while male patients with smoking were significant higher than female patients (36.55% vs 8%). In the full model (model 3), after adjusting for confounding variables, the female AAD patients were more likely to have worse short-term outcomes (OR=3.60, 95% CI=1.41 to 9.60).Conclusion: Female patients were more likely to have worse outcomes in non-surgically managed AAD patients with hypertension. Large numbers of investigations are required to further explore this relationship.Keywords: aortic dissection, gender-differences, hypertension, short-term outcomes